(untitled) (Journal of Governance and Development (JGD), 2016)
Poverty reduction is the most important agenda for the least developed countries such as Pakistan. In spite of the modest economic growth in Pakistan, rural poverty has not been reduced due to various reasons. Poverty is a complex phenomenon and it can be articulated in income and non-income components. This study identifies the factors affecting rural household poverty. The study was based on the primary data which was collected through the multi-stage cluster sampling from the rural areas of the Southern Punjab. The responses were collected through face-to-face interviews and the total two hundred heads of household were interviewed. The incidence of poverty was measured through the headcount ratio. A Logit model was used to analyze the relationship between the dependent and the independent variables. The education, health status within the households, the gender of the household head, female participation ratio in labor market and the access to market are inversely related to the household poverty in the said area, while person per room, the female-male ratio (workers), a distance of school from house and dependence ratio are positively related to poverty incidence. Poverty will be alleviated in rural areas of Pakistan if the government improves the basic infrastructure and the market access facilities as well as enhance the household empowerment of rural people.